Synthesis and Characterization of Bismaleimide Modified Vinyl Ester Monomer-Unsaturated Polyester Intercrosslinked Hybrid Matrices. Issue 4 (May 2013) - Chandramohan, A.; Mandhakini, M.; Dinakaran, K.; Alagar, M.
Intercrosslinked hybrid matrices were developed from N, N′-bismaleimido-4, 4′-diphenyl methane (BMI) modified vinyl ester monomer (VEM), namely cyclohexyl-1, 1′-bis[4-(γ-2-methylphenoxy)-α-hydroxypropylacrylate]-unsaturated polyester (UP) resin. BMI-modified VEM-UP hybrid matrices were characterized for their mechanical properties, viz. tensile strength, flexural strength, unnotched izod impact strength and hardness as per ASTM standards. Data obtained from thermal studies indicated that the introduction of vinyl ester monomer into unsaturated polyester resin marginally reduced the values of heat distortion temperature and glass transition temperature compared with those of the neat UP resin. Scanning electron microscopy studies of BMI modified VEM-unsaturated polyester systems exhibited a homogeneous morphology, confirming efficient chemical interaction and the formation of intercrosslinked networks.